The Book of Tobit: Text, Tradition, Theology : Papers of the First International Conference on the Deuterocanonical Books, Pápa, Hungary, 20-21 May, 2004 - Xeravits, Géza,; Zsengellér, József, (Supplements to the Journal for the Study of Judaism ;, 2005)
This volume contains the proceedings of the first of an international series of conferences on the deuterocanonical literature organised by the Shime'on Centre in Pápa, Hungary. Renowned international scholars of the field treat questions of text in the Book of Tobit, the underlying traditions and theological questions. The importance of the deuterocanonical corpus is widely recognised in contemporary scholarship. This is marked by the growing number of related publications. Yet it remains important to create an opportunity to work through the entire deuterocanonical material as such. These conferences aim to provide a yearly forum for discussion of this literature. The next conferences planned are on Maccabees (2005), Sirach (2006), Wisdom (2007), Additions (2008) and Judith (2009), and as a result, the organisers plan to publish five more volumes. Together with the present volume these will cover the entire deuterocanonical corpus.